Enabling Self-Directed Academic and Personal Wellbeing Through Cognitive Education - Van Tonder, Gideon P.; Kloppers, Magdalena M.; Grosser, Mary M. (Frontiers in Psychology, 2022)
We explore the effectiveness of a Cognitive Education intervention that foregrounds the explicit and purposeful teaching of thinking skills and dispositions to learners to establish its latent potential for enhancing self-directed academic - and personal well-being. We illuminate the qualitative outcomes of an exploratory pilot study with a heterogeneous group of willing in-service teachers from two public primary schools (n = 12), one private primary school (n = 3), and one pre-school (n = 2) in South Africa who received exposure to an 80-hour intervention that comprised seven study units. The article delineates the experiences of the teachers concerning their participation in the intervention as reflected in their written reflections, as well as their perceptions about the value of the intervention that were probed with semi-structured one-on-one interviews after completion of the intervention. The findings revealed that exposure to the intervention that was framed within the principles of Cognitive Education holds benefits for equipping teachers with teaching strategies to create classroom conditions that nurture the development of thinking skills and dispositions that are important for self-regulated academic and personal well-being.